Organic ion template-guided solution growth of ultrathin bismuth oxyselenide with tunable electronic properties for optoelectronic applications - Dang, Le-Yang (2022)
2D Bi2O2Se has recently attracted widespread research interest due to its high electron mobility and good air stability with tunable bandgap. However, the direct and controllable growth of large-size, high-quality ultrathin Bi2O2Se with tunable electronic properties remains a great challenge. Here, an organic ion template-guided solution growth method, is developed using water as a solvent to efficiently obtain high-quality 2D Bi2O2Se. Significantly, the thicknesses and morphologies of 2D Bi2OxSe with various oxygen deficiencies; are also achieved. Optical spectroscopic results indicate that oxygen defects can dramatically tune the electronic properties of Bi2O2Se, such as work function, band gap, and energy-band positions. As a result, the optimized Bi2O2Se devices exhibit a high photoresponsivity of 842.91 A W−1, photo-detectivity of 8.18 × 1012 Jones under 532 nm laser, and electron mobility of 334.7 cm2 V−1 s−1. This work proposes a new green solution method to synthesize large-sized, high-quality Bi2O2Se with tunable electronic structures that can be extended for various applications and provides a new possibility of transfer-free large-scale device manufacturing.